Cankarjev prostorski trikotnik - Kocijan, Gregor (Jezik in slovstvo, 1999)
The article presents the space lived in by Cankar and extending from Vrhnika through Ljubljana to Vienna (the biographic component) and topi in his literature, which are also caught within this triangle. In Cankar's writing, places (and especially countryside) are subordinated to his personal experience and mood, and typically appear in the function of symbolic parallelism.
Keywords: Cankar, Ivan, 1876-1918; history of literature; literarna zgodovina; moderna; Moderna Therapeutics; Slovene literature; slovenska književnost; slovenski pisatelji; študije